Mastigostyla moqueguensis (Tigridieae: Iridaceae), a new species from southern Peru - Huaylla, Hibert (2022)
A new species, Mastigostyla moqueguensis Huaylla & Llalla, is described from the Andes of Moquegua in southern Peru. Mastigostyla, which belongs to the tribe Tigridieae, is widely distributed in the Puna and Andean dry valleys of southern Peru and central Bolivia. The new species can be recognized by its ovate-lanceolate, acute inner tepals with glands at the base. It shows some affnity with M. torotoroensis because of the fliform, bifid style arms with apical stigmas. We present photographs and a table highlighting differences between the new specie and some similar species.